Catalytic upgrading of biomass pyrolysis volatiles to bio-fuel under pre-plasma enhanced catalysis (PPEC) system. (1st November 2018) - Fan, Yongsheng; Zhu, Lei; Fan, Lele; Zhao, Weidong; Cai, Yixi; Chen, Yuwei; Jin, Lizhu; Xiong, Yonglian
Abstract: A catalysis process enhanced by pre-plasma for bio-fuel preparation was proposed. Three aspects were included: (i) the process was analyzed and optimized aiming at comprehensive evaluation index, (ii) the Ti/HZSM-5 was introduced under optimal conditions and mechanism was explored, and (iii) the catalytic stability was evaluated. The results showed catalytic temperature, catalytic height and discharge power had significant effects on the index and interactions were exist. Optimal conditions were catalytic temperature of 455 °C, catalytic height of 26 mm and discharge power of 30 W. The energy consumption of pre-plasma occupied 12.35% of the total. Ti modification decreased the bio-fuel yield from 15.05% to 13.77%, and the oxygen content and calorific value reached 10.95% and 35.50 MJ/kg. The total hydrocarbon content was 52.90% and desired monocyclic aromatic hydrocarbons occupied 64.22%, and 82.84% of hydrocarbons were concentrated in the C10-C13 range. The main oxygenates after upgrading were hydroxyl containing compounds, which were difficult to eliminate due to the high hydrophilicity. The upgrading processed in series, involving reactant activation, catalytic reactions and multiple interactions. The coking rate of spent catalysts decreased from 6.85% to 3.15% after Ti modification, even in the case of that the effective hydrogen to carbon ratio of reactants was lower. Highlights: Pre-plasma enhanced catalysis was firstly investigated in the bio-fuel preparation. Optimization gave 15.05% of bio-fuel yield and pre-plasma consumed 12.35% of energy. Ti modification decreased bio-fuel yield to 13.77% and increased HHV to 35.50 MJ/kg. Total hydrocarbon content reached 52.90% and the desired MAHs occupied 64.22%. Catalyst coking rates decreased from 6.85% to 3.15% under actions of Ti and plasma.